2010
DOI: 10.1021/ar900246s
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Disordered Organic Semiconductors via QM/MM Simulations

Abstract: Organic semiconductors (OSCs) have recently received significant attention for their potential use in photovoltaic, light emitting diode, and field effect transistor devices. Part of the appeal of OSCs is the disordered, amorphous nature of these materials, which makes them more flexible and easier to process than their inorganic counterparts. In addition to their technological applications, OSCs provide an attractive laboratory for examining the chemistry of heterogeneous systems. Because OSCs are both electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 40 publications
1
104
0
Order By: Relevance
“…This is well investigated even for the amorphous Alq 3 system. [16][17][18][19][20] However, these KMC requires quite high computational cost. Meanwhile, we principally present the substitution effect on the transport characteristics with the relatively simple quantum chemistry calculation.…”
Section: Theoretical and Methodologymentioning
confidence: 99%
“…This is well investigated even for the amorphous Alq 3 system. [16][17][18][19][20] However, these KMC requires quite high computational cost. Meanwhile, we principally present the substitution effect on the transport characteristics with the relatively simple quantum chemistry calculation.…”
Section: Theoretical and Methodologymentioning
confidence: 99%
“…For example, this method has been used to calculate charge transfer rates via Marcus theory. 29,3742 In 2000, Kim et al suggested that a charge could be treated via the Langevin equation. 43 Beyond CDFT and LMD, many other models of charge transport in organic semiconductors have been proposed (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the model does not consider actual molecules and it has difficulty in revealing the molecular scale behaviour of carriers; the disorders, which originate from amorphous structures, are used as adjustable parameters to reproduce the experimental mobility data. Although microscopic analyses have also been carried out567891011121314151617181920212223 and some useful suggestions have been derived, we only have a limited understanding of the nature of charge transport in amorphous organic layers. In these studies, Marcus theory24 have frequently been employed to calculate rate constants k ij of intermolecular charge transfer between molecule i and molecule j , described as:…”
mentioning
confidence: 99%